Enhanced contractility of intraparenchymal arterioles after global cerebral ischaemia in rat – new insights into the development of delayed cerebral hypoperfusion. (29th January 2017) - Spray, S.; Johansson, S. E.; Radziwon‐Balicka, A.; Haanes, K. A.; Warfvinge, K.; Povlsen, G. K.; Kelly, P. A. T.; Edvinsson, L.
Abstract: Aim: Delayed cerebral hypoperfusion is a secondary complication found in the days after transient global cerebral ischaemia that worsens the ischaemic damage inflicted by the initial transient episode of global cerebral ischaemia. A recent study demonstrated increased cerebral vasoconstriction in the large arteries on the brain surface (pial arteries) after global cerebral ischaemia. However, smaller arterioles inside the brain (parenchymal arterioles) are equally important in the regulation of cerebral blood flow and yet their pathophysiology after global cerebral ischaemia is largely unknown. Therefore, we investigated whether increased contractility occurs in the intraparenchymal arterioles. Methods: Global cerebral ischaemia was induced in male Wistar rats by bilateral common carotid occlusion for 15 min combined with hypovolaemia. Regional cerebral blood flow was determined by quantitative autoradiography. Intraparenchymal arterioles were isolated and pressurized, and concentration–response curves to endothelin‐1 with and without the endothelin B receptor‐selective antagonist BQ788 was generated. Endothelin B receptor expression was investigated by quantitative flow cytometry and immunohistochemistry. Results: We observed increased endothelin‐1‐mediated contractility of parenchymal arterioles correlating with reduced cerebral blood flow of the cortex, hippocampus and caudate nucleus 48 h after global cerebral ischaemia. The increased endothelin‐1‐mediated contractility was abolished by BQ788, and the vascular smooth muscle cell‐specific expression of endothelin B receptors was significantly increased after global cerebral ischaemia. Conclusion: Increased endothelin‐1‐mediated contractility and expression of endothelin B receptors in the intraparenchymal vasculature contributes to the development of delayed cerebral hypoperfusion after global cerebral ischaemia in combination with vascular changes of the pial vasculature.